2009
DOI: 10.1590/s0034-72802009000400006
|View full text |Cite
|
Sign up to set email alerts
|

Comparison between OPD-scan results and contrast sensitivity of three intraocular lenses: spheric AcrySof SN60AT, aspheric AcrySof SN60WF and multifocal AcrySof Restor lens

Abstract: Purpose: Compare the OPD-scan results and the contrast sensitivity in patients who had implantation of the AcrySof SN60D3 multifocal IOL, the AcrySof SA60AT spheric monofocal IOL and the AcrySof SN60AT aspheric monofocal IOL. Methods: Thirty-two eyes received the multifocal IOL, 32 eyes received the spheric monofocal IOL and 32 eyes received the aspheric monofocal IOL. They were closely paired in age, sex, pre-operative wavefront analysis and contrast sensitivity. All patients was tested with the OPD-scan aber… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0
1

Year Published

2012
2012
2016
2016

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 19 publications
0
2
0
1
Order By: Relevance
“…Nevertheless, it is understood that the same difficulty in measurement was imposed upon both groups, making comparisons reasonable. Hida et al compared the ZM900 and SN60D3 lenses and found similar aberrometric results, as did Nakano et al (10,27) . Moreno et al evaluated a system for analyzing the wavefront of a double-passage Optical Quality Analysis System (Visiometrics, S.L., Cerdanyola, BCN, Spain) that could differentiate the two wavefronts and thereby assess the optical quality more accurately for better differentiation (29) .…”
Section: Discussionmentioning
confidence: 58%
See 1 more Smart Citation
“…Nevertheless, it is understood that the same difficulty in measurement was imposed upon both groups, making comparisons reasonable. Hida et al compared the ZM900 and SN60D3 lenses and found similar aberrometric results, as did Nakano et al (10,27) . Moreno et al evaluated a system for analyzing the wavefront of a double-passage Optical Quality Analysis System (Visiometrics, S.L., Cerdanyola, BCN, Spain) that could differentiate the two wavefronts and thereby assess the optical quality more accurately for better differentiation (29) .…”
Section: Discussionmentioning
confidence: 58%
“…Considering CS, ZA9003 IOL has been considered better than the ZMA00 IOL (10,22,23) . Nakano et al and Vingolo et al concluded the same by comparing SN60WF and SA60AT IOLs with SN60D3 and ZM900 IOLs (27,28) . This phenomenon could be explained through the analysis of the concept of multifocality promoted by these kind of lenses by splitting light energy into two foci and overlapping near and far images.…”
Section: Discussionmentioning
confidence: 79%
“…Segundo dados do Ministério da Saúde, em 2002, foram realizadas, no Sistema Único de Saúde (SUS), aproximadamente 300.000 cirurgias de catarata. Após esse período, impulsionado por benefícios clínicos relacionados a novas tecnologias dos facoemulsificadores (3) e das lentes intraoculares (LIOs) (4)(5)(6)(7)(8) , e por uma maior segurança cirúrgica (9)(10)(11)(12) , houve um aumento no número …”
Section: Introductionunclassified